Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1476-072x-12-53
|View full text |Cite
|
Sign up to set email alerts
|

Using google street view for systematic observation of the built environment: analysis of spatio-temporal instability of imagery dates

Abstract: BackgroundRecently, Google Street View (GSV) has been examined as a tool for remotely conducting systematic observation of the built environment. Studies have found it offers benefits over in-person audits, including efficiency, safety, cost, and the potential to expand built environment research to larger areas and more places globally. However, one limitation has been the lack of documentation on the date of imagery collection. In 2011, Google began placing a date stamp on images which now enables investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 27 publications
3
66
0
1
Order By: Relevance
“…However, the differences shown for cycling infrastructure (cycle storage) may be a temporal issue, whereby new cycling infrastructure (e.g., bicycle parking) in Madrid were not present when the Google Street View imagery was taken. In summary, our findings are compatible with the work of other studies, 45 that have found that the more subjective characteristics (e.g., sidewalk conditions) have lower agreement between virtual and physical audits. However, in our findings view aesthetics and streetscape aesthetics showed an acceptable agreement.…”
Section: Discussionsupporting
confidence: 83%
“…However, the differences shown for cycling infrastructure (cycle storage) may be a temporal issue, whereby new cycling infrastructure (e.g., bicycle parking) in Madrid were not present when the Google Street View imagery was taken. In summary, our findings are compatible with the work of other studies, 45 that have found that the more subjective characteristics (e.g., sidewalk conditions) have lower agreement between virtual and physical audits. However, in our findings view aesthetics and streetscape aesthetics showed an acceptable agreement.…”
Section: Discussionsupporting
confidence: 83%
“…Spatiotemporal instability (Curtis et al 2013) in the Fukushima GSV dataset makes this problematic, however. Signs and barriers at the entrances to highly contaminated areas may suddenly (re)appear or disappear as one transitions without warning from a set of photographs taken at one point in time to imagery of the same place shot months or years later, and other features may disappear completely as images are updated and replaced with newer ones.…”
Section: How Well Can Gsv Be Used To Assess Potentialmentioning
confidence: 99%
“…Indeed, as outlined in Sect. 3 the possibility for GSV to chart recovery from tornadoes, hurricanes, and wildfires has been evaluated (Curtis et al 2013), with Curtis et al (2007) advocating the importance of tracking community return as a means of building resilience post-disaster. Given that the Japanese government is working towards the goal of decontamination in order to resettle at least some of those evacuated from their homes after the 2011 nuclear disaster (Ministry of Environment 2015), it is worth exploring whether GSV tracking over time could be extended to the decontamination and rehabilitation of radioactively-contaminated landscapes as well as natural disaster recovery in order to assess or at least keep abreast of progress.…”
Section: Tracking ''Recovery'' Over Timementioning
confidence: 99%
See 2 more Smart Citations